1998
DOI: 10.1002/hep.510280429
|View full text |Cite
|
Sign up to set email alerts
|

High titers of antibodies inhibiting the binding of envelope to human cells correlate with natural resolution of chronic hepatitis C

Abstract: Most cases of hepatitis C virus (HCV) infection result inHepatitis C virus (HCV) is the most important causative agent of blood-borne non-A non-B hepatitis, infecting a million people a year worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 26 publications
2
77
1
Order By: Relevance
“…36 Antibodies against E2 were detected in 88% of chronically infected and in 49% of acutely infected HCV patients. 37 mAbs have been made from such patients and V region sequences have been determined.…”
Section: Discussionmentioning
confidence: 97%
“…36 Antibodies against E2 were detected in 88% of chronically infected and in 49% of acutely infected HCV patients. 37 mAbs have been made from such patients and V region sequences have been determined.…”
Section: Discussionmentioning
confidence: 97%
“…Mouse and guinea pig sera were tested for their ability to inhibit the binding of E2 protein to human target cells as previously described (25,46). Briefly, NOB titers were determined by incubation of MOLT-4 cells with a nonsaturating concentration of biotinylated I-E2 715 protein (1.5 g/ml), which was previously incubated with a test serum at different dilutions.…”
Section: Methodsmentioning
confidence: 99%
“…Most antibodies that demonstrate broad neutralization of cell binding and/or infection are directed against conformational epitopes within E2. [27][28][29][30][31] Induction of antibodies recognizing conformational epitopes is a challenging task, as these are difficult to mimic, and protein subunit vaccines are more likely to generate strain-restricted responses due to the immuno-dominance of the variable regions. 32 However, we have recently shown that the mouse monoclonal antibody (MAb) AP33 can potently neutralize retroviral pseudo-particles (HCVpp) bearing genetically diverse E1E2 glycoproteins.…”
mentioning
confidence: 99%